Physical Properties of Rice Husk-Pine Wood Particleboard - Zhi Zhi, Low; Te Chuan, Lee; Selimin, Mohamad Ali; Pagan, N.A.; Abdul Halip, Juliana (Journal of Sustainable Materials Processing and Management, 2021)
Rice husk is one types of sustainable and economical agricultural wastes that could produce particleboard as the substitute for solid wood. The problems that encourage this research are due to the increasing of deforestation and the increment demand for solid wood in various industries. Malaysia produces a significant amount of agricultural biomass waste every year. It is noteworthy to mention that agricultural wastes can be fully used in an environmentally friendly way. This study aims to evaluate the properties of particleboard made from rice husk at different fibre loading and mixture. Different formulated composition of rice husk and pine wood shaving was prepared for the production of particleboard by hot pressing at temperature 160 Â°C for 6 min using urea-formaldehyde (UF) resin with additional of ammonium chloride (NH4Cl) as a hardener. The results showed the density values and moisture content of particleboards ranging from 0.547 to 0.660 g/cm3 and 8.072 to 8.929 %, respectively. The thickness swelling and water absorption were increased as the increment of soaking time. Besides, the colour of the rice husk-pine particleboards has no significant difference and changes except for particleboard made from 100% rice husk. While the more proportion of pine wood shaving has the better compaction of particleboards, and the addition of grinded rice husk also make the particleboards have fewer voids. This study is expected to reduce deforestation activities and to maximize the usage of agricultural wastes.